Navigating Two Worlds: Duality, Americanization and the Road to Becoming a Person in Anzia Yezierska’s Bread Givers (1925) - Permanyer Rodríguez, Martina (Journal of Artistic Creation and Literary Research, 2025)
This paper analyses Anzia Yezierska’s depiction of the Jewish American immigrant family in Bread Givers (1925), as well as the main character’s fight for independence in her journey to become a self-sufficient member of the American society. I will argue that Yezierska’s choice to offer a representation of the hazardous life of the Jewish American immigrant young woman suggests the presence of a cultural duality between the traditions of the Old World, principally represented by the protagonist’s father, –an Orthodox rabbi who keeps the modernity of the New World out of his home–; and the aforementioned New World, that, to Sara Smolinsky– the main character of the novel– speaks for the independence that she longs for during her youth. As she herself proclaims, she aims to “become a person” (Yezierska 50), an expression she uses to express her wanting to assert herself as an independent member of the American society, consciously accepting that she will have to face the challenges that exile and patriarchal patterns entail (Bančić 24), but willing to do so in order to become a “real American.”